PROBLEMS AND PROSPECTS OF THE OIL PRODUCTS MARKET IN UKRAINE TODAY AND IN THE POSTWAR PERIOD - Gavrys, Mykola; Nesterenko, Roman; Gavrys, Oleksandr (Honor and Law, 2022)
The article is aimed to identify threats to national security due to the current state of the petroleum products market and factors that affect the cost of fuel in Ukraine during the war and will shape fuel prices in Ukraine and the whole world in the short and medium term. Such factors now are the almost complete absence of the domestic product on the market, the rupture of old logistics chains and problems with the development of new logistics routes for fuel supply from Europe, high world prices for oil and petroleum products, instability of the national currency and risks, associated with the war. It is estimated that the fair price for imported petrol and diesel fuel at the end of May ‒ beginning of June 2022 is 45 UAH in the western regions, and up to 50 UAH per liter in the eastern regions of Ukraine. Factors that will affect prices in the near future include the possible unblocking of Ukraineʼs seaports, oil and petroleum products supplies from the United States, Central Asia and the Middle East, shale oil from the United States, increased market competition and increased demand as a result of the end of COVID-19 crisis. Ukrainian people should be ready to high prices of petroleum products in the near future and the Ukrainian state should prepare the system of national security and national defense for solving of the logistics problems with delivery of the petroleum products and potential social problems.